A Computational Exploration of Electromagnetic Characteristics in Magneto-dielectric Materials - Adhiyoga, Yohanes Galih; Arifin, Tri Nur; Wahyuningsih, Erfiana; Pratiwi, Ganjar Febriyani; Sugeng, Margono (Department of Electrical Engineering, 2024)
Using various new materials in current technological developments, besides providing opportunities for better product development, can also open research opportunities in the world of materials. In the last decade, magneto-dielectric materials have been extensively researched for use in various applications in the high-frequency spectrum. Before it can be implemented as a material that can be used widely, its characteristics must be identified first. This paper proposes the process of characterizing the electrical and magnetic properties of the high-frequency spectrum. Mathematical analysis carried out through simulations has identified the electrical and magnetic properties of the magneto-dielectric material so that the permittivity, permeability, and losses of both dielectric and magnetic can be determined. Based on the analysis results of several magneto-dielectric samples, the permittivity, permeability, and losses are directly proportional to the composition of magnetite (Fe3O4) in the magneto-dielectric material. With these results, the use of magneto-dielectric materials can be increasingly adapted to the electromagnetic properties they have.